Balancing service inclusion for primary and secondary customers experiencing vulnerabilities. Issue 6 (4th August 2021) - Leino, Henna M.; Hurmerinta, Leila; Sandberg, Birgitta
Abstract : Purpose: Secondary customers often experience secondary vulnerabilities that manifest in family-centred transformative services as other- and self-related customer needs. Yet, a relational perspective on primary and secondary customers' needs is lacking. The study analyses secondary customers' needs and their relationship to primary customers' needs to enhance well-being in customer entities. The service inclusion lens is used to understand customers' experiences of vulnerability. Design/methodology/approach: The study uses an exploratory approach. The data consists of ethnographic observations and interviews of elderly residents (primary customers), their family members (secondary customers) and nurses in two nursing homes. Findings: Primary and secondary customers' needs are interrelated (or unrelated) in four ways: they are separate, congruent, intertwined or discrepant . The vulnerability experiences fluctuate in intensity and over time, individually reflecting on these need dimensions. Research limitations/implications: The study contributes to service research concerning customers' experiences of vulnerability, secondary customers and their inclusion in services. Primary customers' service inclusion may increase/decrease secondary customers' service inclusion and their experience of vulnerability. Moreover, secondary customers' inclusion is often necessary to foster primary customers' inclusion and well-being. Practical implications: Fostering service inclusion and well-being for primary and secondary customers requires balanced inclusion and acknowledging the needs of both groups. Service providers may need to act as moderators within customer entities if discrepant needs occur. Originality/value: The study addresses the under-researched areas of family members' customer needs, their relation to primary customers' needs, experiences of secondary vulnerability and context-related vulnerability.